2007
DOI: 10.1128/aem.00453-07
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Wild-Type and Resistant Strains of the Hyperthermophilic BacteriumThermotoga maritimato Chloramphenicol Challenge

Abstract: Transcriptomes and growth physiologies of the hyperthermophile Thermotoga maritima and an antibioticresistant spontaneous mutant were compared prior to and following exposure to chloramphenicol. While the wild-type response was similar to that of mesophilic bacteria, reduced susceptibility of the mutant was attributed to five mutations in 23S rRNA and phenotypic preconditioning to chloramphenicol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…It is a bacteriostatic agent, occasionally also with bactericidal activity, that binds to the 50S ribosomal subunit and blocks the elongation of peptides during the biosynthesis of proteins (39,56). The response to treatments with chloramphenicol in sensitive clinical strains such as Streptococcus pneumoniae (42), Bacillus subtilis (31), Yersinia pestis (51), and Enterococcus faecalis (1) has been analyzed, and it was shown that in addition to protein biosynthesis inhibition, chloramphenicol provokes oxidative stress in sensitive bacteria (1,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a bacteriostatic agent, occasionally also with bactericidal activity, that binds to the 50S ribosomal subunit and blocks the elongation of peptides during the biosynthesis of proteins (39,56). The response to treatments with chloramphenicol in sensitive clinical strains such as Streptococcus pneumoniae (42), Bacillus subtilis (31), Yersinia pestis (51), and Enterococcus faecalis (1) has been analyzed, and it was shown that in addition to protein biosynthesis inhibition, chloramphenicol provokes oxidative stress in sensitive bacteria (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to chloramphenicol may also be due to target site mutation/modification (39), decreased outer membrane permeability (10), and the presence of efflux pumps that often act as multidrug extrusion transporters, thereby reducing the effective intracellular drug concentration (15,53).…”
mentioning
confidence: 99%
“…Although the peptidyl transferase centre is the main target site for many antibiotics and substrate analogs (Spahn & Prescott, 1996), chloramphenicol binds to the 23S rRNA of the 50S ribosomal subunit and blocks the elongation of peptides during biosynthesis of proteins (Montero et al, 2007). Chloramphenicol induces oxida- (Aakra et al, 2010), while β-lactams interfere with the production of peptidoglycan and break the cell of active dividing microorganisms in an iso-osmotic environment (Yellanki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These resistance mechanisms may include altered penicillinbinding proteins, presence of various β-lactamases and loss of porins (Bou & Martïnez-Beltran, 2000). While active efflux and enzymatic inactivation are the mechanisms responsible for resistance to aminoglycosides (Smith et al, 2007), the most common mechanisms of resistance to chloramphenicol are decreased outer membrane permeability (Burns et al, 1989), enzymatic inactivation by acetylation essentially by acetyltransferase or by chloramphenicol phosphotransferases (Schwartz et al, 2004;Aakra et al, 2010), target site modulation (Montero et al, 2007) and presence of efflux pump (Daniels & Ramos, 2009). To overcome various resistance mechanisms and dissemination of antibiotic resistance genes, exploring the possible synergy between conventional antibiotics becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spontaneous mutation characteristics in target genes in Thermusthermophilus (a bacterium) and Sulfolobusacidocaldarius (an archaeon) were found to be comparable, despite the phylogenetic and physiological differences that exist between the two microorganisms (Mackwan et al 2008). Also, a chloramphenicol-resistant, mutant of the hyperthermophilic bacterium Thermotogamaritima containedseveral nucleotide changes in ribosomal genes, resulting in significant transcriptomic differences between the mutant and wild-type during growth in the presence and absence of the antibiotic (Montero et al 2007). Mutations were identified in a laboratory strain of the hyperthermophilicarchaeon, Pyrococcusfuriosus DSM 3638(Bridger et al 2012).…”
Section: Introductionmentioning
confidence: 99%